Stress, repetitive negative thinking, and mental health in Chilean university students: an ecological momentary assessment study - Inostroza, Carolina; Bustos, Claudio; Bühring, Vasily; González, Lorena; Cova, Félix (Frontiers in Psychology, 2024)
Background Mental disorders in university students are a growing attention problem in the international community due to their high prevalence and serious consequences. One possible reason is university students’ difficulties in coping with stress. Repetitive negative thinking (RNT) is a transdiagnostic process that, when combined with stress, can lead to the development of various disorders. We aim to determine the effect of stress and RNT on predicting various mental health syndromes in university students across 7 days. Method Prospective observational study using Momentary Ecological Assessment (EMA) with the OURMIND Mobile App. On day one, 238 university students responded to the SCL-90R questionnaire for symptoms of depression, anxiety, hostility, obsession, psychoticism, paranoia, somatization, and interpersonal sensitivity; RNT styles questionnaires, RRS for rumination and negative reflection, PSWQ for worry; SISCO-II for term academic stress, and sociodemographic. EMA consisted of five assessments a day for 6 days; each time, the students answered items about academic and non-academic stress (EMA-stress), reactive RNT duration and intrusiveness (EMA-RNT process), and reactive RNT rumination, reflection, and worry (EMA-RNT content). On day eight, symptoms were re-assessed. Seven hierarchical stepwise linear regression models were used to test the predictive power of the study variables in the development of SCL-90R symptoms. Results When comparing models, adding baseline symptoms increased the models’ predictive power in all symptom groups. In most cases, including EMA-stress generated greater predictive power, except for paranoia and interpersonal sensitivity. Adding the EMA-RNT process increased the prediction of paranoia and obsessive symptoms; for hostility symptoms, RNT styles increased predictive power. For the final regression models, considering the initial symptoms, the EMA-RNT process predicted the progression of symptoms in six out of eight groups, while EMA-non-academic stress predicted the remaining two. Additionally, living with other relatives or friends was a predictor of depressive symptoms. Discussion The stress of university life impacts the development of psychiatric symptoms in university students. These results provide evidence of RNT as a transdiagnostic process in several syndromic groups. Universal preventive programs should consider the impact of academic and non-academic stress on university students’ mental health. Targeting RNT would also benefit selective preventive interventions.